2010
DOI: 10.1159/000314269
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Innate Immunity Pathways and Their Potential Contribution to the SIRS/CARS Debate: Evidence from Human Studies and Animal Models

Abstract: The lack of a causal and successful treatment for sepsis has led to a re-evaluation of the condition’s pathopysiology. The failure of anti-inflammatory strategies has implied compensatory immunosuppression to play a central part in fatal clinical cases. While searching for novel therapeutic strategies, the question arose whether pro-inflammation (systemic inflammatory response syndrome, SIRS) or anti-inflammation (compensatory anti-inflammatory response syndrome, CARS) are dominant in sepsis, and may be counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 190 publications
0
21
0
Order By: Relevance
“…Interest in the functional consequences of genetic variation in determining susceptibility and response to disease is increasing, also in critical illness (3,4,33,34). Our study of several SNPs spread throughout the MASP1 gene encoding MASP-3 (7,35) identified two SNPs for which the variant allele was associated with higher on-admission MASP-3 levels.…”
Section: Lectin Pathway In Critically Ill Childrenmentioning
confidence: 97%
See 1 more Smart Citation
“…Interest in the functional consequences of genetic variation in determining susceptibility and response to disease is increasing, also in critical illness (3,4,33,34). Our study of several SNPs spread throughout the MASP1 gene encoding MASP-3 (7,35) identified two SNPs for which the variant allele was associated with higher on-admission MASP-3 levels.…”
Section: Lectin Pathway In Critically Ill Childrenmentioning
confidence: 97%
“…The question why some patients are more susceptible to developing these complications than others is intriguing and raises the possibility of genetic predisposition. Certain genetic variants of innate immunity genes would thus orchestrate different responses to apparently similar insults (3,4).…”
mentioning
confidence: 99%
“…( 20 , 21 ) However, a study in mice had shown that previous induction of a low-grade systemic inflammatory response protected the animals from developing sepsis induced by Enterococcus faecalis or methicillin-resistant Staphylococcus aureus . ( 22 ) When initially a severe systemic inflammatory response was induced, severe sepsis developed after infection with microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is generally considered a systemic inflammatory disorder and is a serious clinical problem with high mortality (Hotchkiss and Karl, 2003;Kumpf and Schumann, 2010). It can be defined as a progressive failure of the circulation, characterized clinically by vascular leakage, edema, shock and organ failure (Takukyu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%